Ameica is in the Heart as a Colonial-Immigrant Novel Engaging the Bildungsroman - Gonzales, Gabriel Jose, S.J. (Archīum Ateneo, 2024)
Carlos Bulosan’s America is in the Heart, the first Filipino American novel, has held a special place as one of the first of Asian American literary writing, but its craft has also been questioned because of the plainness of its language and its repetitious, tortuous plot. Through an evaluation and analysis of the novel as a Bildungsroman, this paper argues that the seeming failure of the plot to provide a coherent narrative of development is in itself the literary manifestation of the frustrating socio-economic realities in which the first Filipinos in America lived. Bulosan’s novel is therefore not so much a failed Bildungsroman but a twentieth-century Filipino American engagement of a nineteenth-century form in which the encounter not only uncovers the myth of universality of the form but also asserts the self-representation of the heretofore unrepresented. As such, America is in the Heart needs to be read not only as a record of but as an involvement in the Filipino American struggle in the mid-twentieth century.